2010
DOI: 10.1007/s12031-010-9476-0
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of CSPG3 Accompanies Neuronal Progenitor Proliferation and Migration in EAE

Abstract: The molecular identities of signals that regulate the CNS lesion remodeling remain unclear. Herein, we report for the first time that extracellular matrix chondroitin sulphate proteoglycan, CSPG3 (neurocan) is upregulated after primary inflammatory injury. EAE was induced using myelin oligodendrocyte glycoprotein (MOG) (35-55) which was characterized by massive polymorphonuclear cell infiltration and loss of myelin basic protein expression along with steep decrease of CNPase. Periventricular white matter (PVWM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…Increased neurocan expression is consistent with other reports showing induction of neurocan levels following different types of insults to the mammalian central nervous system, including a knife wound injury to the cortex (Asher et al, 2000;Asher et al, 2002), a contusion injury to the spinal cord (Andrews et al, 2012;Massey et al, 2008) as well as inflammatory insults (Sajad et al, 2011) and chronic glial scars (McKeon et al, 1999). In cell culture, neurocan is anti-adhesive and can effectively repel axons, and these actions were effectively abrogated after treatment of neurocan with chondroitinase ABC, supporting a primary role of GAG chains in actions of neurocan (Friedlander et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…Increased neurocan expression is consistent with other reports showing induction of neurocan levels following different types of insults to the mammalian central nervous system, including a knife wound injury to the cortex (Asher et al, 2000;Asher et al, 2002), a contusion injury to the spinal cord (Andrews et al, 2012;Massey et al, 2008) as well as inflammatory insults (Sajad et al, 2011) and chronic glial scars (McKeon et al, 1999). In cell culture, neurocan is anti-adhesive and can effectively repel axons, and these actions were effectively abrogated after treatment of neurocan with chondroitinase ABC, supporting a primary role of GAG chains in actions of neurocan (Friedlander et al, 1994).…”
Section: Discussionsupporting
confidence: 92%
“…The tight band of 4S CSPG staining around the injury core following CCI is associated with the core proteins neurocan and NG2. Increased neurocan expression is consistent with other reports showing induction of neurocan levels following different types of insults to the mammalian central nervous system, including a knife wound injury to the cortex (Asher et al,2000,2002) and a contusion injury to the spinal cord (Andrews et al,2012; Massey et al,2008) as well as inflammatory insults (Sajad et al,2011) and chronic glial scars (McKeon et al,1999). In cell culture, neurocan is anti‐adhesive and can effectively repel axons, and these actions were effectively abrogated after treatment of neurocan with chondroitinase ABC, supporting a primary role of GAG chains in actions of neurocan (Friedlander et al,1994).…”
Section: Discussionsupporting
confidence: 89%
“…In another model of RR EAE (induced with MOG in C57BL/6 mice) (32,33), it was demonstrated that EAE enhanced the migration of SVZ-derived neural stem/progenitor cells (NSC) to the olfactory bulbs and that the adult mouse SVZ is a source of newly generated oligodendrocytes that may contribute, along with oligodendrocyte precursors, to the replacement of oligodendrocytes in inflammatory demyelinating diseases of the CNS. Because it is highly probable that the same would be valid for RR EAE in SJL/J mice, the activated NSC could then express the TSPO, which would reflect the increased uptake of 18 F-PBR111.…”
Section: Discussionmentioning
confidence: 99%